2017
DOI: 10.3390/ijms18112302
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Locus Genetic Risk Score for Primary Open-Angle Glaucoma (POAG) Variants Is Associated with POAG Risk in a Mediterranean Population: Inverse Correlations with Plasma Vitamin C and E Concentrations

Abstract: Primary open-angle glaucoma (POAG) is a leading cause of blindness worldwide. The genetics of POAG are complex, and population-specific effects have been reported. Although many polymorphisms associated with POAG risk have been reported, few studies have analyzed their additive effects. We investigated, in a southern European Mediterranean population, the association between relevant POAG polymorphisms, identified by initial genome-wide association studies (GWASs) and POAG risk, both separately and as an aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…They found no association between PRS of myopia and POAG ( p = 0.81), VCDR ( p = 0.42), cup area ( p = 0.25), IOP ( p = 0.07), or RNFL thickness ( p = 7.7 × 10 −3 ), demonstrating that there is no evidence for overlap of genetic RFs between POAG and myopia [ 46 ]. Additionally, a 2017 PRS from a southern European Mediterranean population demonstrated a strong association between a PRS of 4 SNPs and POAG (OR: 2.92; 95%CI: 1.79–4.77, p < 0.001), while also showing an inverse correlation between the PRS and low levels of vitamin C ( p = 0.002) and vitamin E ( p = 0.001), suggesting a possible role for oxidative stress mechanisms in the pathogenesis of POAG [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found no association between PRS of myopia and POAG ( p = 0.81), VCDR ( p = 0.42), cup area ( p = 0.25), IOP ( p = 0.07), or RNFL thickness ( p = 7.7 × 10 −3 ), demonstrating that there is no evidence for overlap of genetic RFs between POAG and myopia [ 46 ]. Additionally, a 2017 PRS from a southern European Mediterranean population demonstrated a strong association between a PRS of 4 SNPs and POAG (OR: 2.92; 95%CI: 1.79–4.77, p < 0.001), while also showing an inverse correlation between the PRS and low levels of vitamin C ( p = 0.002) and vitamin E ( p = 0.001), suggesting a possible role for oxidative stress mechanisms in the pathogenesis of POAG [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The earliest studies have demonstrated significant but modest discriminatory powers for a glaucoma PRS. [40][41][42] In 2015, Tham et al 41 developed a glaucoma PRS combining seven IOP-associated and 18 VCDRassociated SNPs known at the time, and reported a modestly higher odds of developing POAG in the top tertile of the PRS relative to the bottom tertile in a multiethnic cohort from Singapore (IOP-PRS OR, 2.50; 95% confidence interval [CI], 1.54-4.02; VCDR-PRS OR, 2.31 [95% CI, 1.50-3.55]). Mabuchi et al 40 conducted an unweighted PRS utilizing nine IOPassociated SNPs in a Japanese cohort and reported a modest association with higher tension POAG (OR per risk allele = 1.12; 95% CI, 1.01-1.24).…”
Section: Primary Open Angle Glaucomamentioning
confidence: 99%
“…Genomic DNAs were extracted from venous blood samples of each participant, which were anticoagulated with ethylenediaminetetraacetic acid (EDTA), by applying approach of phenol‐chloroform extraction and ethanol precipitation. Then, DNA was amplified with the aid of a PCR kit (Takara), and SNPs in MALAT1 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 and ANRIL 14 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 were genotyped using the single‐base end extension (SNaPshot) method, a genetic analyzer (model: ABI3130), and Genemapper software from ABI.…”
Section: Methodsmentioning
confidence: 99%